(untitled) (Global Journals of Research in Engineering, 2024)
An assessment of landuse and landcover LULC patterns and changes at catchment level is crucial to planning and management of dam reservoirs LULC changes over a 30-year period for 9 reservoir catchments in northern Ghana were assessed using a mixed-method approach involving GIS remote sensing technique and key informant interviews Four major LULC namely cropland water bodies built-up land and open savannah woodlands were identified and classified from 1986 1996 2006 and 2016 LandSat TM images of the reservoir catchments Substantial changes in LULC were observed in the reservoir catchments from 1986 to 2016 mainly through the conversion of large areas of closed and open savannah woodlands to cropland and built-up areas Across all the catchments cropland and built-up land increased significantly whilst water bodies open savannah woodland and closed savannah woodland experienced a declined over the past 30-years Between the years 1986 and 2016 cropland and built-up areas increased by 13 80 to 58 88 and 3 17 to 18 82 respectively whereas water bodies and open savannah woodland decreased by 14 28 to 46 03 and 0 17 to 5 29 respectively The driving factors of these changes have been noted as human population farmland expansion deforestation lack of community involvement in the management of the catchments and lack of proper education on catchment management The changes in LULC in the catchments could lead to dramatic changes in the catchment peak flows increase in soil erosion high sediment loads and sedimentation of the reservoirs Good agricultural practices are necessary in the catchment management